U. S. broadcasting to the Soviet Union - by Ludmilla Alexeyeva. (U. S. Helsinki Watch Committee, 1986)
On the work of the Russian-language broadcasting services of Radio Liberty and the Voice of America.Bibliography: p. 133-136.